1997
DOI: 10.1557/jmr.1997.0303
|View full text |Cite
|
Sign up to set email alerts
|

The growth of decagonal Al–Co–Ni single crystals as a function of chemical composition

Abstract: Decaprismatic single crystals taken from a series of alloys of nominal compositions within Al 65277 Co 3222 Ni 3222 have been studied by means of x-ray diffraction techniques. The substitution of Co by Ni in increasing amounts changes the (pseudo)decagonal diffraction patterns drastically and indicates structural changes which range from a single-crystalline approximant via orientationally ordered nanodomain structures and quasiperiodic phases with different types of ordering phenomena, to a basic decagonal ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…An X-ray single crystal study on a series of decaprismatic crystals of compositions Al 65-77 Co 3-22 Ni 3-22 , quenched from 800 C, was performed as function of composition and temperature (Zhang, 1995;Zhang, Estermann, Steurer, 1997;Baumgarte, Schreuer, Estermann, Steurer, 1997 11.3 did not show reflection splitting in the low-resolution X-ray precession photographs but "satellite reflections" which have been shown to be related to twinned domain structures of 1D QC (Kalning, Kek, Burandt, Press, Steurer, 1994;Kalning, Press, Kek, 1995;Kalning, Kek, Krane, Dorna, Press, Steurer 1997). Al 72.7 Co 11.6 Ni 15.7 was superstructure I and Al 70.6 Co 6.8 Ni 22.6 the basic Ni-rich d-phase.…”
Section: X-ray Diffraction and Neutron Scatteringmentioning
confidence: 99%
“…An X-ray single crystal study on a series of decaprismatic crystals of compositions Al 65-77 Co 3-22 Ni 3-22 , quenched from 800 C, was performed as function of composition and temperature (Zhang, 1995;Zhang, Estermann, Steurer, 1997;Baumgarte, Schreuer, Estermann, Steurer, 1997 11.3 did not show reflection splitting in the low-resolution X-ray precession photographs but "satellite reflections" which have been shown to be related to twinned domain structures of 1D QC (Kalning, Kek, Burandt, Press, Steurer, 1994;Kalning, Press, Kek, 1995;Kalning, Kek, Krane, Dorna, Press, Steurer 1997). Al 72.7 Co 11.6 Ni 15.7 was superstructure I and Al 70.6 Co 6.8 Ni 22.6 the basic Ni-rich d-phase.…”
Section: X-ray Diffraction and Neutron Scatteringmentioning
confidence: 99%
“…A reduction of the particle size is expected for longer alloying time. However, an opposite effect is observed, this could be due to the high ductility, stability and structure of the decagonal phase of the system Ni-CoAl [18][19][20][21][22][23] , in addition to the forming a bimodal/multimodal grain size distribution, that improves the ductility of the nanostructured materials 24 .…”
Section: Resultsmentioning
confidence: 99%
“…By systematic variation of the chemical composition of Al± ±Co± ±Ni alloys (Baumgarte et al, 1997;Zhang et al, 1997;Kalning, Kek, Burandt, Press, Steurer, 1994), or by extended annealing (Grushko et al, 1998) a similar transition from periodic to aperiodic state can be observed. This transition is of crucial importance for understanding the formation and growth of quasicrystals.…”
Section: In-situ Measurements At High-temperaturementioning
confidence: 92%
“…(cf. Zhang, Estermann, Steurer, 1997;Baumgarte, Schreuer, Estermann, Steurer, 1997). Although, there are many examples of highly anisotropic diffuse scattering which demand for high resolution in particular directions, high-resolution diffractometry is not necessarily required if resolution in reciprocal space is not the prime issue.…”
Section: Diffuse Scattering In Quasicrystalsmentioning
confidence: 99%
See 1 more Smart Citation